Kualitas Audit Memoderasi Pengaruh Financial Distress pada Manajemen Laba - Utari, Ni Made Sintia; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p07, 2023)
This research aims to determine the effect of financial distress on earnings management with audit quality as a moderating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Sampling in this study used the non-participant observation method, where there were 53 companies that met the sampling criteria. The analysis technique used is Moderated Regression Analysis (MRA). The results of data analysis show that the financial distress variable has a positive and significant effect on earnings management and the audit quality variable is able to weaken the influence of financial distress on earnings management. Keywords: Earnings Management; Financial Distress; Audit Quality